DISTINCTIVE FEATURES OF STORIES BY STEFAN ZWEIG - Asomiddinova Gulbarno Alijonovna (Journals Park Publishing, 2022)
The article analyzes the artistic originality of Stefan Zweig's novels. Special attention is paid to the psychological novel, which studies the types of characters, the depth of emotions, temperament. The novella is a kind of psychological experiment: the author puts his characters in certain conditions and observes their behavior.The main purpose of this observation is to get to know the person. While the most important means of discovering a person’s inner world is psychological analysis, Zwaig uses a variety of linguistic and stylistic tools. The description of these tools is the purpose of the article.
Keywords: S. Tsvayg; novella; psychologize